Data-Driven Innovation for Circular Digital Economy in Sustainable Urban Development - Lukita, Chandra; Handra, Tessa; Oganda, Fitra Putri; Laurens, Mackenzie (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2025)
The rapid advancement of digital technology has transformed how cities innovate and sustain their growth, making data-driven innovation a crucial element in achieving sustainable urban development. This study aims to examine the integration of data analytics, artificial intelligence, and Internet of Things within the framework of a circular digital economy to promote smarter, greener, and more resilient cities aligned with the Sustainable Development Goals. Using a Systematic Literature Review method, the research collected and analyzed publications from 2015 to 2024 obtained from major academic databases such as Scopus, ScienceDirect, and IEEE Xplore. The results show that data accessibility, interoperability, and digital infrastructure enhance efficiency in energy, mobility, and waste management, while digital tracking supports circularity and resource optimization. Governance that applies human-centered design further ensures inclusivity and transparency in urban systems. Overall, the findings highlight that data serves not only as a technological asset but also as a strategic driver for sustainable transformation. The study concludes that integrating data-driven innovation with circular economy principles strengthens collaboration among governments, industries, and communities, enabling cities to achieve long-term sustainability and contribute effectively to global goals such as innovation, responsible consumption, sustainable cities, and climate action.